2019
DOI: 10.1002/agr.21629
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate exposure of agricultural cooperatives

Abstract: Despite the growth of exchange risk literature in the field of agricultural economics, little attention has been paid to firm‐level currency exposure in emerging countries. In this context, this paper investigates the exchange rate exposure faced by a unique data set of 66 Brazilian agricultural cooperatives from 2000 to 2015, and finds that around one‐third of the sampled firms exhibited significant exposure during this period, even after controlling for crises. The paper also documents that the proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Second, the Working Capital Management literature has attracted growing interest in the last 10 years. However, studies focusing on private firms remain scarce, mainly in the case of Emerging Economies, which is an important issue since private organizations account for the vast majority of firms in these countries (Piccoli, 2020). Since this study focuses on a unique dataset of Brazilian private firms, the findings reported here can provide a better understanding of the issues that private emerging organizations face with regard to working capital management.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Second, the Working Capital Management literature has attracted growing interest in the last 10 years. However, studies focusing on private firms remain scarce, mainly in the case of Emerging Economies, which is an important issue since private organizations account for the vast majority of firms in these countries (Piccoli, 2020). Since this study focuses on a unique dataset of Brazilian private firms, the findings reported here can provide a better understanding of the issues that private emerging organizations face with regard to working capital management.…”
Section: Introductionmentioning
confidence: 93%
“…As these are private data, the financial reports were made available without identifying the respective cooperatives to ensure their privacy. Even though our sample is limited to agricultural cooperatives in this state, it is worth mentioning how representative Paran a State is in this industry, since it is responsible for 40% of Brazilian exports of agricultural products and for 30% of the national agricultural GDP (Piccoli, 2020). Furthermore, the agricultural cooperatives are also relevant local agents as they correspond to 56% of the agricultural economy of Paran a, the leading industry in this State (Ocepar, 2016).…”
Section: Datamentioning
confidence: 99%
“…The fact that they belong to this sector is explained by its importance to the local economy. Paran a State is the second largest agricultural producer in Brazil, responsible for around 30% of Brazilian agricultural GDP and 40% of this industry's exports (Piccoli, 2020).…”
Section: Context Of Training In Cooperativismmentioning
confidence: 99%
“…In the recent years, efforts to relate FXE to the firm level distress Prasad et al (2018) show significantly positive relationship between the two. Exposure in the agriculture industry has been studied with significant exposure and risk (Piccoli, 2020). Experts have contributed variously in developing measures and identifying factors and evaluating the impact of the exchange rate exposure from different angles.…”
Section: Literature Reviewmentioning
confidence: 99%